Innovating Mandailing folk tale preservation via Canva-based online comics as student teaching media - Nikmah Sari Hasibuan; Husniah Ramadhani Pulungan; Nurmaini Ginting; Suhailee Sohnui; Cindy Azelia; N. Nanda; Khoiriah Hasanah Nasution (Universitas Muhammadiyah Malang, 2025)
This study aims to use Canva-based online comics as an interactive teaching tool to illustrate Mandailing folklore. The method employed is descriptive analytic, with instrument reliability tested using Cronbach's Alpha, indicating high reliability with an alpha value above 0.7. Data were collected in two stages. The urgency of this research is to examine the impact of technological advancements on local culture, making digital media such as online comics an effective teaching tool. First, oral literature of folklore was recorded, transcribed, and translated into Indonesian. Second, the instrument was applied to students through online comics, which were then quantitatively evaluated to measure student engagement and understanding. Based on research conducted in Mandailing Natal Regency, student engagement at SMP N 1 Panyabungan Utara was 40%, at Tsanawiyah Arriyadul Mukhlisin 33%, and at Pesantren Abinnur Al-Islami 27%. Student enthusiasm was 41% at SMP N 1 Panyabungan Utara, 32% at Tsanawiyah Arriyadul Mukhlisin, and 27% at Pesantren Abinnur Al-Islami. The percentage of students who understood was 38% at SMP N 1 Panyabungan Utara, 33% at Tsanawiyah Arriyadul Mukhlisin, and 29% at Pesantren Abinnur Al-Islami. The percentage of students using this technology was 42% at SMP N 1 Panyabungan Utara, 33% at Tsanawiyah Arriyadul Mukhlisin, and 25% at Pesantren Abinnur Al-Islami. This study examines the conditions at several schools in Mandailing Natal Regency, showing differences in student engagement, enthusiasm, understanding, and technical constraints faced.